Respuesta :

To solve this system of equations, since y is already isolated in both equations, you can set the expressions to equal each other to solve for x:

-x + 2 = - 5x - 6
-x + 5x = -6 - 2
4x = -8
x = -2

Now that we have x, we can substitute it into one of the equations to find y:

y = -(-2) + 2
y = 2 + 2
y = 4

The last step is to substitute both values into both equations to see if they are correct:

4 = -(-2) + 2    -->    4 = 2 + 2    <--True
4 = -5(-2) - 6    -->    4 = 10 - 6    <--True

Answer:
x = -2
y = 4
ACCESS MORE